Silver Nanoparticles against Foodborne Bacteria. Effects at Intestinal Level and Health Limitations - Zorraquín-Peña, Irene (Microorganisms, 2020)
Foodborne diseases are one of the factors that endanger the health of consumers, especially in people at risk of exclusion and in developing countries. The continuing search for effective antimicrobials to be used in the food industry has resulted in the emergence of nanotechnology in this area. Silver nanoparticles (Ag-NPs) are the nanomaterial with the best antimicrobial activity and therefore, with great potential of application in food processing and packing. However, possible health effects must be properly addressed to ensure food safety. This review presents a detailed description on the main applications of Ag-NPs as antimicrobial agents for food control, as well as the current legislation concerning these materials. Current knowledge about the impact of the dietary exposure to Ag-NPs in human health with special emphasis on the changes that nanoparticles undergo after passing through the gastrointestinal tract and how they alter the oral and gut microbiota, is also summarized. It is concluded that given their potential and wide properties against foodborne pathogens, research in Ag-NPs is of great interest but is not exempt from difficulties that must be resolved in order to certify the safety of their use.